Effect of panchagavya with neem to promote green gram and analyse the Biochemical changes (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
To investigate the relationship between panchagavya with Neem and normal plant in green gram. The level of carbohydrate, protein, lipid, and calcium and phosphorous of the green gram seed as influenced by the application of panchagavya with neem. The level of carbohydrate was gradually increased from low concentration to high concentration. Among the concentration tried, the maximum amount was found in 15% (carbohydrate, 10.4 g) and 20% (carbohydrate 14.2g) when compared to control. The levels of protein were slightly elevated from low concentration to high concentration. Among the concentration tried, the maximum amount were found in 15% (protein 11.1 g) and 20% (protein 13.4 g) when compared to control. The level of fat was gradually increased from low concentration to high concentration. Among the concentration tried, the maximum amount was found in 15% (fat 26.8g) and 20% (fat 29.7g) when compared to control. The results of calcium were slowly elevated from low concentration to high concentration. Among the concentration tried, the maximum amount was found in 15% (calcium 9.2g) and 20% (calcium 11.3g) when compared to normal. The level of phosphorous was gradually increased from low concentration to high concentration. Among the concentration tried, the maximum amount was found in 15% (phosphorous 21.2g) and 20% (phosphorous 21.6g) when compared to control.